2015
DOI: 10.1016/j.celrep.2015.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Combined Loss of Tet1 and Tet2 Promotes B Cell, but Not Myeloid Malignancies, in Mice

Abstract: Summary TET1/2/3 are methylcytosine dioxygenases that regulate cytosine hydroxymethylation. Tet1/2 are abundantly expressed in HSC/HPCs and are implicated in hematological malignancies. Tet2-deletion in mice causes myeloid malignancies, while Tet1-null mice develop B-cell lymphoma after an extended period of latency. Interestingly, TET1/2 are often concomitantly downregulated in acute B-lymphocytic leukemia. Here, we investigated the overlapping and non-redundant functions of Tet1/2 in HSC maintenance and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
75
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 38 publications
13
75
1
2
Order By: Relevance
“…Furthermore, studies from two independent groups have shown that combination of Tet2 loss and Jak2V617F resulted in aggressive MPN phenotype through both clonal HSC dominance and expansion of downstream precursor populations [76,77]. Notably, TET2 mutations also cooccur with changes in other TET members or DNMT3A mutations in human acute B-lymphocytic leukemia and T-cell lymphoma [78,79]. Concordant with this, Tet1/2 double-knockout mice developed lethal B-cell malignancies, and Tet2 loss combined with Dnmt3a mutation caused T-cell lymphoma/leukemia in vivo, possibly owing to dysregulated Bcl6/Myc and Notch pathway, respectively [78,80,81].…”
Section: Tet2mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies from two independent groups have shown that combination of Tet2 loss and Jak2V617F resulted in aggressive MPN phenotype through both clonal HSC dominance and expansion of downstream precursor populations [76,77]. Notably, TET2 mutations also cooccur with changes in other TET members or DNMT3A mutations in human acute B-lymphocytic leukemia and T-cell lymphoma [78,79]. Concordant with this, Tet1/2 double-knockout mice developed lethal B-cell malignancies, and Tet2 loss combined with Dnmt3a mutation caused T-cell lymphoma/leukemia in vivo, possibly owing to dysregulated Bcl6/Myc and Notch pathway, respectively [78,80,81].…”
Section: Tet2mentioning
confidence: 99%
“…Notably, TET2 mutations also cooccur with changes in other TET members or DNMT3A mutations in human acute B-lymphocytic leukemia and T-cell lymphoma [78,79]. Concordant with this, Tet1/2 double-knockout mice developed lethal B-cell malignancies, and Tet2 loss combined with Dnmt3a mutation caused T-cell lymphoma/leukemia in vivo, possibly owing to dysregulated Bcl6/Myc and Notch pathway, respectively [78,80,81]. Collectively, these data suggest that functional convergent cooperativity of TET2 mutations and co-occurring disease alleles drives hematopoietic transformation.…”
Section: Tet2mentioning
confidence: 99%
“…This may indicate a neutral effect on B cells. Nevertheless, the development of B-cell acute lymphoblastic leukemia was recently reported in mice with double deletion of Tet1 and Tet2 [33].…”
Section: Lessons From Mice With Modified or Deleted Tet2 Genementioning
confidence: 99%
“…understood, particularly as conditional knockout (KO) of TET1, TET1/2 or TET2/3 in murine hematopoietic cells has profound biological consequences [7][8][9].…”
Section: Introductionmentioning
confidence: 99%